2015
DOI: 10.1021/jacs.5b00313
|View full text |Cite
|
Sign up to set email alerts
|

Elucidation of Two Giants: Challenges to Thick-Shell Synthesis in CdSe/ZnSe and ZnSe/CdS Core/Shell Quantum Dots

Abstract: Core/thick-shell giant quantum dots (gQDs) possessing type II electronic structures exhibit suppressed blinking and diminished nonradiative Auger recombination. We investigate CdSe/ZnSe and ZnSe/CdS as potential new gQDs. We show theoretically and experimentally that both can exhibit partial or complete spatial separation of an excited-state electron-hole pair (i.e., type II behavior). However, we reveal that thick-shell growth is challenged by competing processes: alloying and cation exchange. We demonstrate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
65
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(68 citation statements)
references
References 29 publications
3
65
0
Order By: Relevance
“…For example, Meinardi et al fabricated a large scale‐LSC based on “giant” CdSe/CdS QDs embedded in poly(lauryl methacrylate‐ co ‐ethylene glycol dimethacrylate) (PMMA) polymer with PCE ≈1% . One of the main limitations in the present “giant” QDs is the composition of the shell: to date, most giant QDs are coated with a thick CdS shell, for example, “giant” CdSe/CdS QDs, InP/CdS QDs, PbSe/CdSe/CdS QDs, Ge/CdS, etc . As a consequence, the absorption spectrum is dominated by the shell, which strongly absorbs radiation below 500 nm (bandgap E g of 2.49 eV) covering the UV and partially visible range, strongly limiting the application of LSCs in solar cells.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Meinardi et al fabricated a large scale‐LSC based on “giant” CdSe/CdS QDs embedded in poly(lauryl methacrylate‐ co ‐ethylene glycol dimethacrylate) (PMMA) polymer with PCE ≈1% . One of the main limitations in the present “giant” QDs is the composition of the shell: to date, most giant QDs are coated with a thick CdS shell, for example, “giant” CdSe/CdS QDs, InP/CdS QDs, PbSe/CdSe/CdS QDs, Ge/CdS, etc . As a consequence, the absorption spectrum is dominated by the shell, which strongly absorbs radiation below 500 nm (bandgap E g of 2.49 eV) covering the UV and partially visible range, strongly limiting the application of LSCs in solar cells.…”
Section: Introductionmentioning
confidence: 99%
“…23 This extrapolation was carried out assuming a linear relationship between the 1S absorbance peak location and molar extinction coefficient. 24 For example, ZnSe cores with a 1S absorbance peak at 354 nm and a diameter of 3.4 nm were assumed to have a molar extinction coefficient of ε354 nm = 1.6 *10 5 L M -1 cm -1 .…”
Section: Znse Nanocrystal Synthesismentioning
confidence: 99%
“…[89] The early work using QDs was hampered by processes like (1) fluorescence intermittency (blinking); (2) non-radiative Auger recombination of electron-hole pairs; and (3) difficulties in reproducible batch-to-batch synthesis of particles with a consistent size and shape. [94,95] Recent reports have shown that the quantum yield for QD emission can be improved by forming a shell a few atomic layers thick that is composed of a larger bandgap material (e.g., a core of CdSe and a shell of ZnS). [89,94] Approaches to more fully establish control of particle size, shape, and layer composition are contingent, in part, upon the development of and/or application of exacting approaches to particle characterization discussed in the main focus of this paper.…”
Section: Emission-based Detectionmentioning
confidence: 99%